(untitled) (Anclajes, 2022)
In Ricardo Piglia’s Los diarios de Emilio Renzi, there is a multiple negotiation between the autobiographical writing of the three hundred and twenty seven notebooks throughout his life, the work of editing and fictionalizing them in three volumes, the paratexts and the set of stories inserted throughout the narration. This negotiation, which is both a procedure and a compositional effect, entails friction between different times and on two levels. On the one hand, at the enunciative level: the original notebooks; the writing of the book and its publication between 2015 and 2017, and each of the three volumes (Años de formación, Los años felices and Un día en la vida). On the other hand, the level of what is represented: the thematization of the passage of time, certain anachronisms, the temporality of the fictional stories. Thus, differential temporalities are configured in life, the newspaper writing and the fiction that, over the long duration include transtemporal nuclei. From this temporal proliferation, I propose, between the documentary and the fictionalized, what I call the life effect, which suspends both the autobiographical and that assigned to literatura.